Effects of Pretreatment Exposure to Dental Practice Using a Smartphone Dental Simulation Game on Children's Pain and Anxiety: A Preliminary Double-Blind Randomized Clinical Trial - Razieh Meshki; Leila Basir; Fatemeh Alidadi; Azam Behboudi; Vahid Rakhshan (Tehran University of Medical Sciences, 2018)
Objectives: Studies on modeling a pre-exposure technique for the prevention of anxiety in children are rare, and there is no study on interactive modeling using computer games. We assessed the effect of playing a dental simulation game before operation on pain and anxiety in 4- to 7-year-old children during their first dental treatment session. Materials and Methods: In this double-blind randomized clinical trial, 50 children needing unilateral pulpotomy and placement of stainless-steel crowns (SSC) on mandibular primary first molars were enrolled and randomly divided into experimental (a simulation game) and control (no intervention) groups. The experimental group played the game twice a day for two weeks before the scheduled visit. At the dental session, their pre- and post-operative pains were recorded using the Wong-Baker Facial Rating Scale (W-BFRS). Also, heart rate (HR; as an indicator of anxiety) was measured using a finger pulse oximeter at six treatment stages: (1) baseline (at the initial session, two weeks before treatment) and (2-6) during different stages of treatment. Effects of playing the simulation on pain and HR were analyzed using t-test and repeated-measures two-way analysis of covariance (ANCOVA). Results: Game playing significantly reduced the HR (P=0.031). The interaction of playing with the treatment period was also significant (P=0.004). When the groups were compared in each of the six time points, the experimental group showed reduced HR during anesthetic injection and cavity preparation using a high-speed handpiece (P<0.003). Conclusions: Based on the results, playing certain dental simulation games before the first dental visit might reduce the anxiety felt during anesthetic injections and drilling.